Characterization of organophosphate pesticide sorption of potato peel biochar as low cost adsorbent for chlorpyrifos removal - Singh M.; Rano S.; Roy S.; Mukherjee P.; Dalui S.; Gupta G.K.; Kumar S.; Mondal M.K. (My University, 2025)
There has been a growing interest in the scientific world in the production of biochar from natural organic wastes as potential sustainable precursors for bioremediation. Potato peel biochar was produced by slow pyrolysis method under oxygen-limited conditions and used as bio adsorbent in bioremediation of commercial pesticide having Chlorpyrifos as an active component. Chlorpyrifos is an organophosphate pesticide, highly neurotoxic, and primarily targets the central nervous system of pests and insects. The excess residues of chlorpyrifos are hazardous to environmental flora and fauna. Chlorpyrifos was treated against biochar at varying physical parameters and further optimized by using response surface methodology through Box-Behnken design (BBD). 72.06% of pesticide removal was observed post 24 h of treatment against a pesticide concentration of 1346.85 μg/ml with a biochar concentration of 1.04 mg/ml under room temperature at pH 5.04. Biochar was characterized by proximate and ultimate analysis, FTIR, and SEM-EDX. Characterization by SEM-EDX showed the surface morphology and minerals on the peel and biochar. Microgram of potato peel shows pores of larger size than biochar having many cavities with different dimensions. In the plant system, growth morphology, nutritional status, polyphenols, total antioxidant content, and free radical scavenging activity were assessed. Enhancement in presence of biochar was recorded in growth morphology and plant biomolecules including photosynthetic pigments. Better translocation of the nutrient is recorded in biochar treated plants, as evidenced by the low amount of carbohydrate and protein in treated leaves. Biocompatibility assessment of chlorpyriphos in fish erythrocytes showed 43.26% hemolysis by pesticide-treated biochar. The practical use of this approach can also be best utilized if applied to those geographical regions where the soil pH is acidic. Biochar is a marketable bio-product, which can have a positive impact in agriculture, industries, and the energy sector creating a bio-based economy with reduced environmental pollution. © 2022 Elsevier Ltd